2016
DOI: 10.1016/j.meegid.2016.06.017
|View full text |Cite
|
Sign up to set email alerts
|

Overview of HIV molecular epidemiology among people who inject drugs in Europe and Asia

Abstract: HIV strains continuously evolve, tend to recombine and new circulating variants are being discovered. Novel strains complicate efforts to develop a vaccine against HIV and may exhibit higher transmission efficiency and virulence, and elevated resistance to antiretroviral agents. The United Nations Joint Programme on HIV/AIDS (UNAIDS) set an ambitious goal to end HIV as a public health threat by 2030 through comprehensive strategies that include epidemiological input as the first step of the process. In this co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 237 publications
(334 reference statements)
0
21
1
3
Order By: Relevance
“…This research took place in Odessa, a large city in southern Ukraine, which is one of the areas where injection drug use and then an HIV epidemic began in the 1990s and then spread throughout the country. The HIV epidemic in Odessa, as in Ukraine generally, has been a concentrated one with PWID the key population with the most cases until 2008 . Harm reduction programmes increased in size and effectiveness from 2004 and were showing signs of having leveled the epidemic off , though there are worries that recent social movements and the war in Eastern Ukraine may have reversed this.…”
Section: Methodsmentioning
confidence: 99%
“…This research took place in Odessa, a large city in southern Ukraine, which is one of the areas where injection drug use and then an HIV epidemic began in the 1990s and then spread throughout the country. The HIV epidemic in Odessa, as in Ukraine generally, has been a concentrated one with PWID the key population with the most cases until 2008 . Harm reduction programmes increased in size and effectiveness from 2004 and were showing signs of having leveled the epidemic off , though there are worries that recent social movements and the war in Eastern Ukraine may have reversed this.…”
Section: Methodsmentioning
confidence: 99%
“…However, recent studies have reported the emergence and rapid increase of non-B subtypes in various populations globally (Cuevas et al, 2009;Liao et al, 2009;Hawke et al, 2013;Neogi et al, 2014;Beloukas et al, 2016;Nikolopoulos et al, 2016;Dennis et al, 2017), especially among men who have sex with men (MSM) in China (Zhang et al, 2015). CRF01_AE, CRF_BC and Subtype B/B' are most prevalent in Mainland China (Su et al, 2014), and CRF01_AE has recently replaced subtype B as the dominant circulating subtype among Chinese MSM (Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 It is estimated that 36.7 million people globally were living with HIV in 2016, with a prevalence of 0.8%, of which 25.5 million people live in sub-Saharan Africa (~70% of the global HIV burden). 3 , 4 In South Africa, it is estimated that seven million people are living with HIV, with an adult prevalence rate of 19.2% in 2015. 4 , 5 Despite many obstacles faced by South Africa between 2010 and 2014, the response to the AIDS epidemic resulted in the largest antiretroviral treatment (ART) programme in the world, with over two million HIV-infected people receiving treatment by 2010.…”
Section: Introductionmentioning
confidence: 99%